THE ROLE OF SPIRITUAL VALUES IN THE LIFE OF SOCIETY - Boybekova Shaxnoza Aliyevna (International Journal of Literature and Language Studies, 2026)
the article interprets the content and forms of spiritual values in the context of social progress. According to the author, such an approach makes it possible to vividly reveal the original content of spiritual values.